REPRESENTATION DISCRIMINATION OF WOMAN ROLE IN DOCUMENTARY FILM “SURGA KECIL DI BONDOWOSO” (SEMIOTIC ANALYSIS BY ROLAND BARTHES) - Anastasya, Selaya; Sunarto, Sunarto; Bayu Widagdo, Muhammad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The documentary film